(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
نستعرض في بحثنا هذا أهم العوامل المؤثرة على بعض الخصائص الهيدروكيميائية للمياه الشاطئية لمدينة اللاذقيّة وتأثيرها على نوعية المياه وآلية عمل هذا النظام البيئي. تغطي نتائج هذا البحث الفترة الممتدّة بين عام 1991 وعام 1997، ونخلص من خلاله إلى إمكانية التمييز بين ثلاث حالات مختلفة للمياه الشاطئية لمدينة اللاذقيّة من حيث درجة تأثرها بالملوّثات البرّية تبعاً لمواصفات هذه المياه وموقعها الجغرافي. كما تشير النتائج إلى ضرورة إجراء الرصد المستمر لنوعية المياه الشاطئية ومخلّفات مختلف أنواع الأنشطة البرّية تفادياً لأي تغيّرٍ بخصائص هذه المياه يمكن أن يعود عليها بآثارٍ سلبية ويهدد الحياة القائمة فيها. We present in our paper the principal factors affecting some hydrochemical characteristics of coastal water of Lattakia city, the relationship with the water quality and the functioning mechanism of the ecosystem. The reported results cover the period between 1991 – 1997 they permit to distinguish between three different cases of coastal water, in relation to the water quality and the geographical location. They also affirm the necessity to establish a continuos survey plan of coastal water quality and liquid wastes of different land based activities, to avoid any dramatic modifications of hydrochemical coastal water characteristics, which can threat the coastal marine life.